The Concept of Reason as the Controller of the Self and the Formation of Character in Islamic Education: A Conceptual Analysis Based on al-Ghazali’s Ihya’ Ulum al-Din - Yahya, Fata Asyrofi; Basuki Basuki (MA'ALIM: Jurnal Pendidikan Islam, 2026)
Abstract This article examines the concept of reason in Imam al-Ghazali's thought and its relevance to character education in contemporary Islamic education. The background of this research stems from the tendency to reduce rationality in modern education, which emphasizes cognitive and instrumental dimensions and often neglects moral and spiritual dimensions in shaping the character of students. This study aims to analyze the concept of reason as a controller of the nafs in al-Ghazali's perspective and explain its relevance to the development of character education in contemporary Islamic education. This study uses a qualitative approach with a literature review method through conceptual analysis of al-Ghazali's works, especially Ihya 'Ulum al-Din, as well as relevant academic literature. The results of the study show that reason in al-Ghazali's thinking functions as a moral guide that controls the impulses of the nafs and becomes the foundation for the integration of cognitive, moral, and spiritual dimensions in character education. The limitations of this study lie in its conceptual approach, which has not been empirically tested in educational practice. The novelty of this study lies in the reconstruction of al-Ghazali's concept of reason as an integrative framework for the development of character education in the context of contemporary Islamic education. Abstrak Artikel ini mengkaji konsep akal dalam pemikiran Imam al-Ghazali dan relevansinya bagi pendidikan karakter dalam pendidikan Islam kontemporer. Latar belakang penelitian ini berangkat dari kecenderungan reduksi rasionalitas dalam pendidikan modern yang lebih menekankan dimensi kognitif dan instrumental sehingga sering mengabaikan dimensi moral dan spiritual dalam pembentukan karakter peserta didik. Penelitian ini bertujuan menganalisis konsep akal sebagai pengendali nafs dalam perspektif al-Ghazali serta menjelaskan relevansinya bagi pengembangan pendidikan karakter dalam pendidikan Islam kontemporer. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka melalui analisis konseptual terhadap karya al-Ghazali, terutama Ihya’ ‘Ulum al-Din, serta literatur akademik yang relevan. Hasil penelitian menunjukkan bahwa akal dalam pemikiran al-Ghazali berfungsi sebagai pengarah moral yang mengendalikan dorongan nafs dan menjadi fondasi integrasi antara dimensi kognitif, moral, dan spiritual dalam pendidikan karakter. Keterbatasan penelitian ini terletak pada pendekatan konseptual yang belum diuji secara empiris dalam praktik pendidikan. Nilai kebaruan penelitian ini terletak pada rekonstruksi konsep akal al-Ghazali sebagai kerangka integratif bagi pengembangan pendidikan karakter dalam konteks pendidikan Islam kontemporer.